2011
DOI: 10.1007/s11664-011-1791-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated-Temperature Annealing Effects on AlGaN/GaN Heterostructures

Abstract: The effect of high-temperature annealing of undoped AlGaN/GaN heterostructures on different substrates was systematically studied between 1100°C and 1230°C. An AlN spacer layer was found to add stability to structures on sapphire substrates. AlGaN/GaN heterostructures on SiC substrates demonstrated excellent robustness for the temperature range studied, maintaining their mobility, sheet resistance, and sheet concentration values, even after annealing. A silicon nitride, SiN x , capping layer was found to assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The decrease in electron sheet density of sample D is due to the extra long term RTA process. And it has been reported that the high temperature RTA process decreases 2DEG carrier density and mobility [15], [16]. However, the same situation did not occur in sample B.…”
Section: Methodsmentioning
confidence: 88%
“…The decrease in electron sheet density of sample D is due to the extra long term RTA process. And it has been reported that the high temperature RTA process decreases 2DEG carrier density and mobility [15], [16]. However, the same situation did not occur in sample B.…”
Section: Methodsmentioning
confidence: 88%